1995
DOI: 10.1002/app.1995.070550603
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gamma‐irradiation on structural and mechanical properties of polypropylene yarn

Abstract: SYNOPSISPolypropylene multifilament yarn samples were irradiated by gamma rays in air. The effect of radiation dose on thermal, structural, and mechanical properties was studied. Melting endotherms and crystallization exotherms gave useful information regarding the structural changes. X-ray diffraction, infrared spectroscopy, density, and viscosity data of the irradiated samples were analyzed. Although viscosity and mechanical properties decreased with irradiation, the density marginally increased. Breaking el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 19 publications
4
8
0
Order By: Relevance
“…appended for comparison. The XRD spectra confirms the known a-monoclinic form of polypropylene and the prominent peaks observed at 2h = 14°, 17°, 18.5°and 22°corre-spond to (1 1 0), (0 4 0), (0 3 0) and (0 4 1) planes, respectively [18]. It is observed from the figure that there is a successive growth in the intensity of crystalline peaks with the ion fluence.…”
Section: Methodssupporting
confidence: 79%
“…appended for comparison. The XRD spectra confirms the known a-monoclinic form of polypropylene and the prominent peaks observed at 2h = 14°, 17°, 18.5°and 22°corre-spond to (1 1 0), (0 4 0), (0 3 0) and (0 4 1) planes, respectively [18]. It is observed from the figure that there is a successive growth in the intensity of crystalline peaks with the ion fluence.…”
Section: Methodssupporting
confidence: 79%
“…7 shows the typical XRD spectra of pristine, gamma-irradiated, plain-iodinated and radiation-iodinated PP for the period of 48 h. Similar trends were observed for the other periods. The XRD spectrum of pristine PP confirms its a-monoclinic form and the prominent characteristic peaks observed at 2h values of 14°, 17°, 19°and 22°are due to (1 1 0), (0 4 0), (1 3 0) and (0 4 1) planes, respectively [40]. There are no differences in the XRD spectra of pristine and gammairradiated PP, however, it is clearly observed that the intensity of all the XRD peaks considerably decreases in the case of plainiodinated as well as radiation-iodinated PP.…”
Section: Xrd Analysissupporting
confidence: 56%
“…Four peaks occur at 2θ ß14°, 16.94°, 18.5°, and 25.5°corresponding to (110), (040), (130), and (041) planes, respectively. 18,19 The XRD pattern of pristine PP sample conforms to the pattern reported by Mishra et al 20 The highly intense peak at 2θ ß16.94°signifies that the polymer is semicrystalline in nature. It is observed in case of carbonirradiated samples (Fig.…”
Section: X-ray Diffraction Studiessupporting
confidence: 82%